PENERAPAN QUICK ON THE DRAW DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR EKONOMI SISWA KELAS XII IPS 2 SMA NEGERI 2 PEKANBARU: Application Of Quick On The Draw In Learning Cooperative Learning Outcomes For Improving Economy Class XII IPS 2 SMA Negeri 2 Pekanbaru - Ratna Tini (Perspektif Pendidikan dan Keguruan, 2016)
This research is a classroom action research that aims to improve the learningprocess and improve learning outcomes of economics students with the application ofQuick On The Draw in cooperative learning. The subjects were students of class XIIIPS 2 SMA Negeri 2 Pekanbaru in the first semester of the academic year 2013/2014,totaling 40 people, consisting of 19 male students and 21 female students withacademic ability levels are heterogeneous. The study consisted of two cycles, eachcycle consisting of four phases: planning, implementation, observation and reflection.Each end of the cycle carried out daily tests. The data collection is done byobservation techniques and techniques written test. Data was analyzed usingdescriptive qualitative analysis techniques of narrative and descriptive statisticalanalysis. Results of research on the observation sheet shows the activity of teachersand students have done well after taking action even though there are still somedeficiencies. Teacher activity in accordance with the planning and activities ofstudents also increased to be active both in discussions and when answering aquestion card set. Criteria for success of the action on this study is the result ofincreased student learning that can be seen from the increasing value of students canbe seen from the analysis of the achievement of KKM. If the number of students whoreach KKM on daily tests 1 and 2 daily test more than the basic score, it can be saidShiva value increases. The number of students who reach KKM on a base score, dailytest I (first cycle), daily test II (second cycle) respectively are 30%, 50% and 75%. Theresults of this study indicate that the application of Quick On The Draw incooperative learning can improve student learning outcomes economy class XII IPS 2SMA Negeri 2 Pekanbaru semester of academic year 2013/2014.